GLOBALNY PROBLEM ŻYWNOŚCIOWY - TYPOLOGIA KRAJÓW WEDŁUG STOPNIA NIEDOŻYWIENIA - Poczta, Walenty; Pawlak, Karolina; Dec, Maria (Wydział Prawa i Administracji UAM, 2008)
There is a significant difference in economic development and food production worldwide, the result of which is food shortages, undernourishment and starvation on the one hand, and constant excess of food production and excessive food consumption, on the other. The main aim o f the paper was to assess the food situation in the regions affected by food shortages, and to recommend some ways in which their situation could be improved. The analysis was based on the data available from the Food and Agriculture Organisation of the United Nations (FAO) which covered 107 countries inhabited in 2003 by a total of 814 million starving or undernourished people, accounting for 95% of the total population suffering from starvation or undernourishment. Using the methods of a cluster analysis, those countries have been grouped under 8 different but internally uniform typological categories. At the same time the complexity and multidimensional aspect of the issue has been indicated.
GLOBAL FOOD PROBLEM - TYPOLOGY OF COUNTRIES BASED ON THE UNDERNOURISHMENT LEVEL